2011
DOI: 10.3390/ijms12129125
|View full text |Cite
|
Sign up to set email alerts
|

Swelling-Activated Anion Channels Are Essential for Volume Regulation of Mouse Thymocytes

Abstract: Channel-mediated trans-membrane chloride movement is a key process in the active cell volume regulation under osmotic stress in most cells. However, thymocytes were hypothesized to regulate their volume by activating a coupled K-Cl cotransport mechanism. Under the patch-clamp, we found that osmotic swelling activates two types of macroscopic anion conductance with different voltage-dependence and pharmacology. At the single-channel level, we identified two types of events: one corresponded to the maxi-anion ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 43 publications
1
36
1
Order By: Relevance
“…As in our previous study of mouse thymocytes [24], we induced cell swelling by employing the hypertonic pipette solution (made by adding mannitol) rather than the hypotonic bath solution, since under this experimental design the whole-cell configuration was more stable and reproducible, and thereby swelling-induced macroscopic currents could be consistently observed. As shown in a representative recording, the macroscopic current developed after attaining the whole-cell configuration using the hypertonic pipette solution, and gradually increased with cell swelling reaching a steady-state level after about 3 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our previous study of mouse thymocytes [24], we induced cell swelling by employing the hypertonic pipette solution (made by adding mannitol) rather than the hypotonic bath solution, since under this experimental design the whole-cell configuration was more stable and reproducible, and thereby swelling-induced macroscopic currents could be consistently observed. As shown in a representative recording, the macroscopic current developed after attaining the whole-cell configuration using the hypertonic pipette solution, and gradually increased with cell swelling reaching a steady-state level after about 3 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell isolation was performed as described previously [24][26]. Briefly, the 6–8 weeks old rats were anaesthetized with halothane or diethyl ether and painlessly euthanized by cervical dislocation; the thymi were dissected and carefully washed with an ice-cold Ringer solution.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that many cells and, among them, immunocells are able to slowly down regulate their volume after a rapid swelling under hyposmotic conditions [59]. It is well recognized that potassium and chloride transport [38] typically contribute to RVD in several cell types and specifically in immunocells, such as thymocytes from rats [59] and mice [60] as well as lymphoblastic leukemia cells [44]. Interestingly it has also been suggested that in Mytilus galloprovincialis digestive cells [35] and in Mytilus californianus gill cells [61] K + and Cl _ cooperate in RVD by the efflux of these two ions followed by an obliged efflux of water from the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 8A and B visualize representative cells with blebbing DCPIB (20 µM). Since DIOA blocks Cl - -channels [3,22] as well as KCC [3,22,23,24,25,26], these may cause an imbalance in Cl - or intracellular pH homeostasis, because Cl - -channels and transporters are also permeable to HCO 3 - [9,27]. …”
Section: Resultsmentioning
confidence: 99%
“…Na + /H + -exchangers, Cl - /HCO 3 - -exchangers and Na + /K + /2Cl - -cotransporters are sorted to the leading edge. Because blockers of I Cl, swell may block Cl - -channels as well as KCCs, as DIOA does [3,22,26,37], and Cl - -free conditions affects several Cl - -dependent transport proteins like KCCs, NKCCs [22,38], the contribution of these different ion channels and transporters to engulfment pseudopodium formation remains to be characterized. Since all blockers used in the present study suppress at least Cl - -channel activity [3,22,37,39] and lamellipodium formation, we conclude that Cl - -channels contribute significantly in lamellipodium formation.…”
Section: Discussionmentioning
confidence: 99%